2006
DOI: 10.1080/03008200600584090
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Initiating Microsplit on the Resistance to Compression-Induced Rupture of the Articular Surface

Abstract: Cartilage-on-bone samples from bovine patellae containing a defined stellar or linear initiating split in the articular surface were incrementally loaded in direct compression with intervening rehydration, until articular surface rupture occurred. All patellae were either normal or exhibited a mild level of surface fibrillation. In all cases the actual loading site was free of disruption. The average rupture stress of the healthy cartilage was significantly higher than that of the mildly degenerate cartilage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“… Flachsmann et al (2006 ) subjected cartilage-on-bone samples to compression using an indenter (8 mm diameter). They found that introducing cracks about 1 mm in length in the superficial layer of cartilage reduced the compressive strength to less than half of the value measured from samples without cracks.…”
Section: Discussionmentioning
confidence: 99%
“… Flachsmann et al (2006 ) subjected cartilage-on-bone samples to compression using an indenter (8 mm diameter). They found that introducing cracks about 1 mm in length in the superficial layer of cartilage reduced the compressive strength to less than half of the value measured from samples without cracks.…”
Section: Discussionmentioning
confidence: 99%
“…2 Our finding of increased ratio of storage to loss stiffness with frequency is consistent with a previous study 11 and the increased susceptible to failure of cartilage at higher rates of loading. 36…”
Section: Discussionmentioning
confidence: 99%
“…For example, both compressive stress and the level of in-plain strain have been investigated and shown to induce rupture. [12][13][14][15] Rupture rates increased with increasing peak stress and varied with strain-rate. 16 Removing fluid from cartilage mechanically, either through pre-loading or creep compression of cartilageon-bone specimens, reduces the likelihood of surface rupture.…”
Section: Introductionmentioning
confidence: 99%